Effect of ageing and income on health care expenditure in Singapore. - Lim, Pei Shan. (2008)
Singapore is facing an ageing population due to longer life expectancies and declining birth rates. This has led to the issue of increasing expenditure on healthcare given an increasingly affluent and ageing population.